When scott got lost - Oldfield, Jenny; Farrow, Martina (Hodder Children's London, 2002)
Fun, quirky, contemporary diary series by a million selling author. In this story, Tiffany goes on a disastrous school trip, then her brother gets lost ... Read on - if you can get hold of a copy!